Toxic Relationship: Depressive Disorder in Adolescents in Pariaman City - Bunga Surya Azzahra; Mega Adyna Movitaria (International Journal of Research, 2023)
This research was motivated by the existence of adolescents who experience depressive disorders triggered by cases of Toxic Relationships. The purpose of this study was to find out how the relationship between Toxic Relationship cases and depressive disorders in adolescents. This research uses qualitative methods. Data was collected by means of case studies, observations and questionnaires. The exact location of the study is at SMA Negeri 1 Pariaman. With the number of respondents as many as 27 adolescents aged 16-17 years. Using data analysis techniques, namely data reduction, display, and verification. The results of this study state that there is a relationship between Toxic Relationships that can cause depressive disorders for adolescents who experience it.